2023
DOI: 10.3389/fgene.2023.1118889
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling DNA damage repair-based molecular subtypes, tumor microenvironment and pharmacogenomic landscape in gastric cancer

Abstract: Objective: The current molecular classification system for gastric cancer covers genomic, molecular, and morphological characteristics. Non-etheless, classification of gastric cancer based upon DNA damage repair is still lacking. Here, we defined DNA damage repair-based subtypes across gastric cancer and identified clinicopathological, tumor microenvironment and pharmacogenomic features.Methods: Unsupervised clustering analysis was executed in the TCGA-STAD cohort based upon the transcriptional expression prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Bioinformatic analysis revealed that CYTL1 contains a signal peptide at the N-terminus encompassing amino acid residues 1-22, which is structurally similar to the secreted chemokine interleukin (IL)-8 4 . Emerging evidence attributes multiple physiological activities to CYTL1, including chemotactic and proangiogenic activities 5 . Human neuroblastoma (NB) cells have been reported to exhibit excess CYTL1 expression in tumor tissues and cell lines, whereas CYTL1 de ciency suppresses SH-SY5Y NB cell proliferation (CP), cell migration (CM), and cell invasion (CI) 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Bioinformatic analysis revealed that CYTL1 contains a signal peptide at the N-terminus encompassing amino acid residues 1-22, which is structurally similar to the secreted chemokine interleukin (IL)-8 4 . Emerging evidence attributes multiple physiological activities to CYTL1, including chemotactic and proangiogenic activities 5 . Human neuroblastoma (NB) cells have been reported to exhibit excess CYTL1 expression in tumor tissues and cell lines, whereas CYTL1 de ciency suppresses SH-SY5Y NB cell proliferation (CP), cell migration (CM), and cell invasion (CI) 6 .…”
Section: Introductionmentioning
confidence: 99%